2017
DOI: 10.31234/osf.io/c8ze3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlated individual differences suggest a common mechanism underlying metacognition in visual perception and visual short-term memory

Abstract: Adaptive behavior depends on the ability to accurately introspect about one’s own performance. Whether this metacognitive ability is supported by the same mechanisms across different tasks is an open question that has thus far been investigated with a focus on correlating metacognitive accuracy between perceptual and long-term memory paradigms. Here, we investigated the relationship between metacognition of visual perception and metacognition of visual short-term memory (VSTM), a cognitive function thought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…As VWM uncertainty is defined as the width of one’s belief distribution over possible stimulus values (memorized location) or the subjective sense of the quality of one’s own memory, uncertainty can fluctuate across trials even when remembering the exact same stimulus. In line with previous behavioral studies 5,7,9,12,13 , we found that uncertainty judgements tracked the quality of VWM on a trial-by-trial basis ( Fig. 5D and 5E ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As VWM uncertainty is defined as the width of one’s belief distribution over possible stimulus values (memorized location) or the subjective sense of the quality of one’s own memory, uncertainty can fluctuate across trials even when remembering the exact same stimulus. In line with previous behavioral studies 5,7,9,12,13 , we found that uncertainty judgements tracked the quality of VWM on a trial-by-trial basis ( Fig. 5D and 5E ).…”
Section: Discussionsupporting
confidence: 92%
“…Access to the uncertainty in our working memory enables us to use the extent to which we 'trust' our memory to make better decisions. Indeed, people's reported confidence in their working memory performance correlates with the magnitude of memory errors, reflecting their ability to track the quality of their memory 5,[7][8][9] . Moreover, people incorporate knowledge of working memory uncertainty to improve their decisions in change detection tasks 6,10,11 and post-memory wagers 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study corroborate those of previous studies and extend them by providing evidence that people maintain uncertainty and use it implicitly and in a way that is behaviorally beneficial . This is in contrast to studies that asked participants to make explicit reports such as confidence ratings ( Rademaker et al., 2012 ; Vandenbroucke et al., 2014 ; Samaha & Postle, 2017 ), because use of uncertainty in these tasks is neither implicit nor behaviorally beneficial (i.e., your confidence rating doesn't affect your performance). Tasks such as the “choose best” ( Fougnie et al., 2012 ; Suchow et al., 2017 ) and wager paradigms ( Yoo et al., 2018 ; Honig et al., 2020 ) use uncertainty in a performance-relevant way, but it is arguable whether this use of uncertainty is implicit.…”
Section: Discussionmentioning
confidence: 88%
“…An intuitive first place to look is the literature on working memory confidence, since confidence can be thought of as a readout of uncertainty. Experimenters have probed memory confidence by asking people to provide a rating ( Rademaker et al., 2012 ; Vandenbroucke et al., 2014 ; Samaha & Postle, 2017 ), choose the best remembered item ( Fougnie et al., 2012 ; Suchow et al., 2017 ), or make a memory-based bet ( Yoo et al., 2018 ; Honig et al., 2020 ). These studies have demonstrated that people have higher working memory confidence on trials that are remembered more accurately (but see Sahar et al., 2020 ; Bona et al., 2013 ; Bona & Silvanto, 2014 ; Vlassova et al., 2014 ; Maniscalco & Lau, 2015 ; Adam & Vogel, 2017 ; Samaha et al., 2016 , for conflicting results), and a computational model in which memory judgments and confidence ratings are derived from the same underlying memory precision can quantitatively account for these joint data ( van den Berg et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that the theory we are testing proposes that both illusions are based on the same mechanisms of alpha-band sampling, this would predict a strong correlation between the two illusion magnitudes. Our group has published similarly sized samples when investigating individual differences in theoretically-large associations (Samaha & Postle, 2015, 2017). However, we sought to quantify more precisely the degree of evidence in favor of the null hypothesis provided by our results by using Bayesian analyses (described later).…”
Section: Methodsmentioning
confidence: 99%